Tsunami Hydrodynamic Force on a Building Using a Sph Real-Scale Numerical Simulation - Cruchaga-Ssa., M (Springer, 2020)
One of the most important aspects in tsunami studies is the behaviour of the wave when it approaches the coast. Information on physical parameters that characterize waves is often limited because of the difficulties in achieving accurate measurements at the time of the event. The impact of a tsunami on the coast is governed by nonlinear physics, such as turbulence with spatial and temporal variability. The use of the smoothed particle hydrodynamic method (SPH) presents advantages over models based on two-dimensional shallow waters equations, because the assumed vertical velocity simplifies the hydrodynamics in two dimensions. The study presented here reports numerical SPH simulations of the tsunami event which occurred in Coquimbo (Chile) in September, 2015. On the basis of the reconstruction of the physical parameters that characterized this event (flow velocities, direction and water elevations), calibrated by a reference model, the force values on buildings in the study area were numerically calculated and compared with an estimate given by the Chilean Structural Design Standard. Discussion and conclusions of the comparison of both methodologies are presented, including an analysis of the influence of the topographic details of the model in the estimation of hydrodynamic forces. © 2019, Springer Nature B.V.